Interactive resources of metadiscourse markers in good and weak undergraduate essays - Radzuwan, Ab Rashid; Amaal Fadhlini, Mohamed (2019)
Metadiscourse in writing is the linguistic signals and expressions used by a writer to organise a text while connecting with readers. This paper reports a preliminary study conducted to discover the existence of metadiscourse markers from interactive resources category, in good and weak persuasive essays written by year two undergraduate students at a selected public university in Malaysia. In the interpersonal model of metadiscourse introduced by Hyland (2005), the two main categories of metadiscourse are interactive and interactional resources. This study focuses on interactive metadiscourse because the markers in this category assists a writer to help the flow of ideas in a text. A collection of undergraduate essays from a public university in Malaysia was collected to create two corpora of 269 good 271 and weak essays, yielding a total number of 143, 407 and 143, 285 tokens respectively. These essays were taken from the participants’ final examination answer scripts for English course at the end of second semester of their study. The metadiscourse markers in the students’ essays were searched with the aid of a concordance software, WordSmith 5.0. More items of metadiscourse markers are found in good essays as compared to the weaker essays. This finding shows that the different quality of essays and their ratings affect the frequency of metadiscourse markers in the essays. However, based on the sub-categories of metadiscourse, only two sub-categories (transitions and code glosses) were found higher in the good essays while the other three (frame markers, endophoric markers and evidentials) were higher in the weak essays. Thus, the level of awareness and needs in using such metadiscourse markers are different between these two corpora. This study is hoped to path way for further studies on the use of metadiscourse in Malaysian undergraduates’ essays.